Improving Students’ English Telephone Skills Of The 11th Grade Of Madrasah Aliyah Al-Washliyah Using Blended Learning Model - TryUtami Arbaiah; Ashari P Swondo (Universitas Potensi Utama, 2022)
The objective of this research was to improve students’ English Telephone Skills using blended learning model. This research was conducted at Madrasah Aliyah Swasta Al-Washliyah Percut. The findings of the study are expected to encourage eduactors’ awareness of english telephone skills using blended learning model and to be useful to give alternative solution in building good communication in english telephone. The subjects of this research were 20 students at eleven grade, the researcher used the Class Action Research (CAR) method. The researcher obtained qualitative data and quantitative data, the result show the improvement students’ English telephone skill using Blended Learning model there were 75,00% who passed the Minimum Mastery Criteria >75. This resulted come from data in the first cycle I and cycle II. In the cycle I pre-test I there were 5 students who succeed with percentage 59,50%and in post-test, there were 11 students who succeed with percentage 72,75%.